Integrated framework of curriculum mapping through keyword tagging using Orange: public service logic approach - Fairus Faqih; Imam Yuadi (Pustaka Karya : Jurnal Ilmiah Ilmu Perpustakaan dan Informasi, 2026)
Comparable to other public service domains in which service provision involves a wide array of resource-integrating actors, higher education faces the challenge of delivering meaningful educational experiences. Adopting a service-logic perspective, this study proceeds from the assumption that such experiences can be shaped through the co-production of library services aligned with course curricula. Public Service Logic (PSL) provides the conceptual foundation for this co-creative integration, while the operationalization employs keyword tagging and relevance modeling in a case study of library practice at Politeknik Perkapalan Negeri Surabaya (PPNS). The analysis uses a neural network configured with a hidden layer of 100 neurons, ReLU activation, the Adam optimizer, L2 regularization (alpha), a specified maximum number of iterations, and a fixed random state. The model achieved precision and recall of 70 percent, indicating successful projection of similarity and relevance between the book collection and course offerings. Theoretically, the study advances the service-logic narrative in higher education by demonstrating integration of library resources with curriculum design